2022
DOI: 10.3389/fmolb.2022.781619
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomics and Metabolomics Analyses of Stress-Induced Murine Hair Follicle Growth Inhibition

Abstract: Psychological stress plays an important role in hair loss, but the underlying mechanisms are not well-understood, and the effective therapies available to regrow hair are rare. In this study, we established a chronic restraint stress (CRS)-induced hair growth inhibition mouse model and performed a comprehensive analysis of metabolomics and transcriptomics. Metabolomics data analysis showed that the primary and secondary metabolic pathways, such as carbohydrate metabolism, amino acid metabolism, and lipid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In order to investigate the potential regulatory effects of CRS on the expression levels of NTS and Ntsr in the skin tissues, we subjected mice to a daily 6‐h confinement in 50 mL conical tubes for a duration of 20 days. This experimental model was implemented without subjecting the mice to physical compression, as previously described in our published work 6,18 . The skin tissues were harvested and subjected for transcriptomics analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the potential regulatory effects of CRS on the expression levels of NTS and Ntsr in the skin tissues, we subjected mice to a daily 6‐h confinement in 50 mL conical tubes for a duration of 20 days. This experimental model was implemented without subjecting the mice to physical compression, as previously described in our published work 6,18 . The skin tissues were harvested and subjected for transcriptomics analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This experimental model was implemented without subjecting the mice to physical compression, as previously described in our published work. 6,18 The skin tissues were harvested and subjected for transcriptomics analysis. As shown in Figure 1A, CRS significantly dysregulated a vast of genes expression in the skin tissues of mice.…”
Section: Crs Inhibited the Gene Expression Levels Of Neurotensin (Nts...mentioning
confidence: 99%
“…PLS‐DA analysis method is a supervised learning method, which is more accurate for the hypothetical data analysis than the unsupervised learning method [49] . Meanwhile, PLS‐DA has a more obvious advantage in regression modeling with variable multiple correlation, fewer samples and more variables [50] . In PLS‐DA analysis, variables with VIP values greater than 1 are considered as important variables [51] .…”
Section: Methodsmentioning
confidence: 99%
“…[49] Meanwhile, PLS-DA has a more obvious advantage in regression modeling with variable multiple correlation, fewer samples and more variables. [50] In PLS-DA analysis, variables with VIP values greater than 1 are considered as important variables. [51] OPLS-DA analysis method eliminates the orthogonal and Y variables on the basis of PLS-DA, [52,53] and OPLS-DA analysis has better clustering grouping ability than PLS-DA.…”
Section: Chemometrics Analysismentioning
confidence: 99%
“…This research illustrates that variation in the amounts of amino acids, TCA cycle intermediates, fatty acids, cofactors, vitamin-related metabolites, and xenobiotics can be reflected in alterations in the hair metabolome during pregnancy [ 5 ]. Wang et al reported that the skin of rats in the chronic restraint stress (CRS) group showed significant modifications in the primary and secondary metabolic pathways of carbohydrate metabolism, amino acid metabolism, and lipid metabolism through the metabonomic analysis of hair growth induced by CRS in rats [ 6 ]. Each functional state of the skin has its specific metabolite pattern, which can also reflect the underlying cells and mechanisms of action [ 7 ].…”
Section: Introductionmentioning
confidence: 99%